Paradoxical delay of senescence upon depletion of BRCA2 in telomerase‐deficient worms. Issue 10 (7th September 2016) - Kwon, Mi‐Sun; Min, Jaewon; Jeon, Hee‐Yeon; Hwang, Kwangwoo; Kim, Chuna; Lee, Junho; Joung, Je‐Gun; Park, Woong‐Yang; Lee, Hyunsook
Abstract : BRCA2 is a multifunctional tumor suppressor involved in homologous recombination (HR), mitotic checkpoint regulation, and telomere homeostasis. Absence of Brca2 in mice results in progressive shortening of telomeres and senescence, yet cells are prone to neoplastic transformation with elongated telomeres, suggesting that BRCA2 has positive and negative effects on telomere length regulation along the path to tumorigenesis. Using Caenorhabditis elegans as a model, we show here that depletion of BRC‐2, an ortholog of BRCA2, paradoxically delays senescence in telomerase‐deficient mutant worms. Telomerase‐deficient worms ( trt‐1 ) exhibit early replication senescence due to short telomeres. It should be noted that worms mutated in brc‐2 are not viable as well due to massive genotoxic insults. However, when BRC‐2 is depleted by RNA interference in trt‐1 mutant worms, the number of generations is unexpectedly increased with telomere length maintained, compared to telomerase mutants. Interestingly, depletion of other HR genes such as rad‐51 and rad‐54 exhibited similar effects. In worms doubly deficient of telomerase and brc‐2, rad‐51, or rad‐54, extra telomeric C‐circles were generated, suggesting that abrogation of HR induces an alteration in telomere environment favorable to illegitimate telomere maintenance when telomerase is absent. Collectively, absence of BRC‐2 in telomerase‐deficient background first leads to telomere shortening, followed by an induction of an as‐yet‐unknown telomere maintenance pathway, resulting in delay of senescence. The results have implications in the understanding of dysfunctional BRCA2‐associated tumorigenesis. Abstract : Telomerase‐deficient mutant worms exhibit early cessation of generations due to telomere shortening. Worms deficient in BRC‐2, an ortholog of tumor suppressor BRCA2, are not viable due to massive genotoxic insults. Here, we show that depleting BRC‐2 in telomerase‐deficient worms paradoxically delays senescence, associated with the induction of an illegitimate telomere maintenance mechanism, similar to alternative lengthening of telomeres (ALT) in human cancers.